Effects of heme–PrP complex on cell-free conversion and peroxidase-linked immunodetection of prions in blood-based assays. (August 2015) - Soutyrine, Andrei; Yogasingam, Nishandan; Huang, Hongsheng; Mitchell, Gordon
Abstract: Prion protein (PrP) binding to natural and synthetic porphyrins has been previously demonstrated but the effects of endogenous heme interactions with PrP remain uncertain. This study investigated implications of this interaction in blood-based peroxidase-linked prion immunodetection and seeded conversion of cellular prion (PrP C ) into disease associated form (PrP Sc ). Heme binding to recombinant PrP C enhanced intrinsic peroxidase activity (POD) by 2.5-fold and POD inherent to denatured blood accounted for over 84% of luminol-based substrate oxidation in a prion immunodetection assay. An immuno-capture assay showed that 75–98% of blood POD was attributable to binding of PrP C with endogenous heme. Additionally, 10 μM heme inhibited ( P  < 0.05) the seeded conversion of PrP C to PrP Sc through the protein misfolding cycling amplification assay. We conclude that the observed effects can interfere with cell-free conversion and peroxidase-linked immunodetection of prions in blood-based assays. These results indicate that heme–PrP interactions could modulate intrinsic POD and protect PrP C from conversion into PrP Sc . Highlights: Direct interaction between heme and PrP leads to enhanced peroxidase activity. Catalytic potential of heme–PrP complex can interfere with peroxidase-based immunodetection of PrP Sc . Heme protects PrP C from abnormal structural changes. Heme can inhibit cell-free seeded conversion of PrP C into PrP Sc .